Интеллектуальное моделирование Е-готовности информационной экономики - Макарова, М.В. (Управляющие системы и машины, 2016)
Рассмотрены принципы когнитивного моделирования и когнитивная модель готовности страны к информационной экономике (E-готовности). Проведена экспертная формализация модели применительно к Украине, дана оценка начального вектора управляющего воздействия на E-готовность и интерпретированы результаты его приложения. Проведен мониторинг изменения базисних факторов когнитивной модели с появлением новых технологий и изменениями в социально-экономической жизни Украины. The article’s aim is to summarize the results of the monitoring expert formalization of the cognitive readiness assessment model of Ukraine to the Information Economy (E-readiness) and to identify the new significant factors of the cognitive model for 2016. It could help to form recommendations for changes in the national ICT strategy of Ukraine. The essential factors that determined the level of E-readiness of Ukraine ten years ago were: level of education, related with network technologies; investments in telecommunications infrastructure (public and private, venture capital); public policy to support the telecommunications business; innovations in the telecommunications industry. The management by these factors formed a critical point of impact on the E-readiness of Ukraine. The tools of cognitive modeling are also suitable for the dynamic tracking and adjustment options of the national ICT strategy. This idea prompted the return to studies in 2016 and hold a justification of such model today. Statistical processing of expert estimations, PEST-analysis and SWOT-analysis of the problem domain demonstrated other factors of the cognitive model of E-readiness of the country than decade ago. Now, however, we were interested not so much in the results of calculating the critical point of the impact of new factors on the E-readiness of Ukraine at the present stage, as in the definition of the new basic factors of the cognitive model. In 2016, they have become more numerous, their relationships are more complicated that indicates the growing maturity of ICT processes in the country. This conclusion is self-sufficient at this stage of research. The future research involves forming of cognitive graph of the more complicated model, iterative calculations in the software, the interpretation of the results of such calculations and publication of the findings, which will be received. Розглянуто принципи когнітивного моделювання та когнітивна модель готовності країни до інформаційної економіки (E-готовності). Проведено експертну формалізацію моделі стосовно України, подано оцінку початкового вектора керувального впливу на E-готовність та інтерпретовано результати його застосування. Проведено моніторинг змін базисних факторів когнітивної моделі з появою нових технологій і змінами у соціально-економічному житті України.